Screening and Prediction of Potential Compounds from Virgin Olive Oil Acting on Proteins Associated with Cancer Disease - Achmad Rodiansyah (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Virgin olive oil contains phenolic compounds that were potential for anti-inflammatory and cancer treatment. Computational biology is a beneficial method to understand how this compound can affect the biological process in humans. This research is conducted by the potential screening of VOO compounds, constructing the pharmacological network and enrichment, and docking simulation. The enrichment result showed that the EGFR, BRAF, MAPK1, CCND1, and MDM2 protein have multiple cancer contributions and related pathways. The docking simulation result showed that the interaction of EGFR-luteolin, BRAF-luteolin, MAPK1-luteolin, CCND1-apigenin, and MDM2-1-hydroxypinoresinol has the highest binding affinity. Further research with the in-vitro method is required to check the reliable mechanisms of each compound to their protein target.